Effect of Polyethylene Pyrolysis Oil Hydrotreatment on the Pt/Al2O3 Catalyst: Experimental Characterization - Adamou, Panayiota; Harkou, Eleana; Bumajdad, Ali; De Jong, Xander; Van Haute, Maarten; Constantinou, Achilleas; Al-Salem, Sultan Majed (My University, 2024)
The dramatic increase in plastics production, coupled with a low recycling and recovery rate, has been a major challenge for sustainable practices and combating climate change. Hydrotreatment processing to upgrade fuel oils is a well-known process in the petroleum industry. In this work, we aim to investigate the catalyst properties before and after the hydrotreatment of pyrolysis oil derived from plastics, namely, linear low-density polyethylene, as no such report is available in the literature. Granular and powder forms of the Pt/Al2O3 catalyst were used in this study with characterization methods executed as such: transmission electron microscopy, X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and IR-RIS. XRD data show that the crystallinity of the catalyst support was unaffected by the hydrotreatment without any residues left, as the characteristic diffraction peaks were indicated for the crystalline phase of the support as 37.4, 39.8, 46.3, and 67.3°. In addition, the TGA experiments revealed that the carbon deposition on the spent catalyst was higher, as indicated by the higher weight loss (15.359%) compared to the fresh catalyst sample (11.43%). XPS analysis showed that the carbon deposition is more intense on the granular spent catalyst, as the intensity of the peaks is some 15 times greater than the peaks from the fresh catalyst. Also, compared to the observed peaks of the powder catalyst, less coke is formed. The band at 1624.05 cm-1 from the IR-RIS spectra was attributed to a shifted C=O band from the coke formation. The extension of these investigations using different catalysts to improve their characteristics and performance and to inhibit coke deposition will contribute to the incorporation of such processes in industry as well as the cost of fuels.
Keywords: Catalysts; Coke; Platinum; X-ray photoelectron spectroscopy